Is Brazil Reversing the Decline in Childhood Immunization Coverage in the Post-COVID-19 Era? An Interrupted Time Series Analysis - Ramon Costa Saavedra; Rita Carvalho-Sauer; Enny S. Paixao; Maria Yury Travassos Ichihara; Maria da Conceição Nascimento Costa; Maria da Glória Teixeira (Vaccines)
Background: The COVID-19 pandemic had significant impacts on healthcare systems, including the disruption of essential services such as childhood immunization. Containment measures, such as social distancing, contributed to reduced adherence to vaccination programs, increasing the risk of re-emerging vaccine-preventable diseases. We aim to assess the evolution of childhood vaccination coverage in Brazil from 2010 to 2024, identifying trends before, during, and after the COVID-19 pandemic. Methods: An interrupted time series (ITS) study was conducted using publicly available aggregated data on vaccination coverage for children under one year of age. Prais–Winsten regression models were applied to estimate trend changes and evaluate the impact of the pandemic on immunization levels. Results: The findings indicate a progressive decline in vaccination coverage between 2010 and 2019, which was intensified in 2020 by the pandemic. The BCG vaccine showed the greatest decline (−24.88%, p < 0.001), while pentavalent and hepatitis B vaccines decreased annually by −3.72% and −2.21%, respectively. From 2021 onwards, a gradual recovery in coverage was observed, with significant increases for BCG (+7.48% per year, p < 0.001), hepatitis B (+7.45%, p = 0.014), and MMR (+6.73%, p = 0.017) vaccines. Discussion: The results highlight a concerning decline in childhood immunization, exacerbated by the pandemic but showing recent signs of recovery. This scenario underscores structural challenges within the National Immunization Program, requiring coordinated efforts to reverse vaccination losses and ensure system resilience in the face of future crises.